Effects of strength and conditioning on critical velocity in running and soccer - Karsten, B. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
A regular strength training should be an integral part of the coaching process in team sports such as football. To-date no research has investigated the effects of such training on the velocity-duration relationship of Critical Velocity (CV). Objectives: To examine the effects of a moderate intensity strength training on changes in CV and sprint performances in recreationally trained football players. Methods: two football teams were divided in a football training only group (FO; n = 13 : 19 ± 1 127 yr., height 177.3 ± 5.2 cm, body mass 73.2 ± 7 kg). and a strength and football training group (ST; n=13: 18 ± 1 yr., 126 height 174.8 ± 5.4 cm, body mass 72.4 ± 6.6 kg). Both groups were tested for values of CV and 30-m sprint time prior and post training intervention. The ST group performed a concurrent 6-week upper and lower body strength and football training, whilst the FO group performed a football only training. Results: after the re-test of all variables, the ST demonstrated significant improvements for CV values by 0.32 m/s (95% C.I. = 0.16 233 to 0.48; p=0.000) after completing the specific training, with no significant changes in the SO group. 30-m sprint performance were slightly improved in the ST group (p=0.078, 0.12 m/s, 95% CI = -0.25 to 0.15) with FO players significantly worsening their performance (p=0.000) by about 0.98 m/s (95% CI = -1.11 to -0.84). Conclusions: combining a 6-week moderate strength training with football training significantly improves CV, whilst moderately improving 30-m sprint performances in non-previously resistance trained male football players. An integrated regular strength training can consequently be recommended to coaches to enhance critical velocity and sprint performances in football.